TiO2-PDMS composite sponge for adsorption and solar mediated photodegradation of dye pollutants. (August 2018) - Hickman, Renae; Walker, Eric; Chowdhury, Sanchari
Graphical abstract: Highlights: TiO2 /PDMS composite sponge efficiently remove toxic dye compound from waste water. The dye is removed via synergistic effects of adsorption and photocatalytic degradation. The composite sponges are cost-effective and biocompatible and recyclable. Abstract: A hydrophobic composite sponge with photocatalytic property is fabricated combining porous polydimethylsiloxane (PDMS) structure and semiconductor TiO2 nanocatalyst. The porous PDMS structures are prepared using sugar as a sacrificial template. The typical size of the pores in the sponge varies from 10 μm to 100 μm. The surface and the pore wall of the PDMS sponge are decorated with TiO2 nanoparticles which are mostly present as an aggregate. These PDMS composite sponges were shown to remove organic pollutants such as the toxic dye Rhodamine B from water efficiently and selectively, via synergistic effects of adsorption and photocatalytic degradation. These sponges first remove a significant amount of the dye from solution by adsorption (∼50% removal) even in the absence of light. Upon exposure to solar light, the dye adsorbed on the surface of the TiO2 -PDMS sponge was photocatalytically degraded, resulting in the further removal of the dye from solution (total 80% removal). The overall dye removal efficiency TiO2 -PDMS composite sponge is comparable with that of a similar amount of the TiO2 in solution. However, the application of composites eliminates the need for complicated separation of the powder catalyst from the solution. Most importantly these composite sponges could be easily regenerated by exposing them to solar light. The excellent performance and the recyclability of these cost-effective TiO2 -PDMS sponges suggest their promising applications in textile wastewater treatment.